VERBAL AGGRESSION OF TEENAGERS AS AN OBJECT OF SOCIAL-PEDAGOGICAL PREVENTION - Неля Перхайло (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
The problem of verbal aggression in social-pedagogical process is described in the article. Socio-pedagogical work is based on different types and forms of communication and requires some skills to build effective communication. Thus the essence of the communicative behaviour of the various participants in the socio-pedagogical process such as social pedagogue, students, parents is revealed. Тhe article highlights some aspects of the problem of verbal aggression in the professional work of a social pedagogue in the process of the formation of its professionally-communicative competence, skills of constructive, assertive behavior. The task was to identify the reasons of verbal aggression in the socio-pedagogical activity and its features; to analyse the mechanisms of protection against verbal aggression; to systematize the methods of disease prevention and verbal aggression in the field of professional activity of the social pedagogue.